Prospettive contemporanee nel dibattito italiano sull’estetica del digitale - Manera, Lorenzo (Aesthetica Preprint, 2021)
The interactive dimension that characterizes the digital sphere, the perceptual aspects that define our relationship with technological devices, and the reconfiguration of the sensitive experience are receiving increasing attention in the Italian contemporary aesthetic debate. On the one hand, this contribution aims to critically examine how the spreading of neo-technologies is redefining the perceptual experience. On the other hand, by presenting the main perspectives on digital aesthetics developed within the Italian context, the paper focuses on the issues and the aspects that might contribute to foster an interactive relationship between digital technologies, human subjects, and the environment. Finally, this contribution aims to both highlight how such perspectives can inform the advancement of new forms of aesthetic education in the digital age, and to define some specific aspects that might contribute to its development.